Pengaruh Teknik Relaksasi Napas Dalam Terhadap Nyeri Post Sectio Caesarea di RSUD Rupit: Effect of Deep Breath Relaxation Technique on Post Sectio Caesarea Pain at Rupit Hospital - Tria Nopi Herdiani; Desi Fitriani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction : Labor by Sectio Caesarea, the mother will experience mild to severe pain. Pain will cause feelings of discomfort, if this is not addressed immediately it will interfere with the healing process and in an effort to reduce pain in caesarean section patients, one of them is using deep breathing relaxation techniques that can reduce the pain scale in post Sectio Caesarea.The purpose of the study was to determine the effect of deep breathing relaxation techniques on post sectio caesarea pain in Rupit Hospital. Method : This study uses a pre-experimental research design with a one group pretest posttest design. The population of this study were all postoperative sectio caesarea patients who received treatment in the Aster Room of Rupit Hospital. Sampling using purposive sampling in this study a sample of 20 postoperative sectio caesarea patients. The data in this study are primary data using a pain scale sheet and secondary data using patient medical records. Hypothesis prereqisite test using Shapiro Wilk test. The hypothesis test used is the Paired Sample T-Test. Result : from univariate data obtained an image of post sectio caesarea the average pain before being given deep breathing relaxation techniques was 5.30 and after being given deep breathing relaxation techniques 2.85. From the bivariate data on the normality test of the pain scale before and after deep breathing relaxation (p > 0.05), the data were normally distributed. And the Paired Sample T-Test hypothesis test found p-value < 0.000. Conclusion : there is an effect of deep breathing relaxation techniques on post sectio caesarea pain in Rupit Hospital.